Accuracy of Audit Opinion: Factors that Influence it - Reschiwati Reschiwati; Maria Christina Leda Meo Maria Christina Leda Meo (Journal of Accounting Research, Organization and Economics, 2019)
Objective – The accuracy of providing audit opinions is very important for stakeholders in the context of business decision making. In order to provide the right opinion, the auditor must have sufficient expertise, independence and experience to support his work. This study aims to analyze the influence of the factors of expertise, independence and experience of auditors on the accuracy of giving audit opinions.Design/methodology – Data collection techniques used in this study are primary data in the form of questionnaires distributed to auditors working in public accounting firms in the Central Jakarta area. The population in this study was 61 KAPs located in Central Jakarta registered in the IAPI 2019 directory. Sampling in this study used a purposive nonprobability sampling technique. There are 78 auditors working in 15 KAP in central Jakarta selected as respondents. This study uses Structure Equation Models (SEM) to achieve the objectives.Results - The results showed that all factors tested namely expertise, independence and experience of auditors affect the accuracy of giving audit opinions, both partially and simultaneously.